Bean commodity corridors scaling up production and market expansion for smallholders in Sub-Saharan Africa - Birachi, Eliud Abucheli; Rubyogo, Jean-Claude; Abang, Mathew M.; Kalemera, Sylvia Monica; Fungo, Robert; Nchanji, Eileen Bogweh; Mukankusi, Clare; Buruchara, Robin Arani; Mutua, Mercy Muli; Onyango, Patricia Atieno (2023)
More structured production, distribution, and trade are important in upgrading bean value chains for higher trade volumes, farmer incomes, and national revenue. A strategic intervention to achieve these goals efficiently and effectively involves the use of a commodity corridor approach. Commodity corridors are areas of bean intensification characterized by flows of products from production to consumption points. These intensification zones are characterized by significant bean activities that include production, distribution, and consumption, and are supported by vast networks of actors. Sub-Saharan African has a low and declining share in the global trade of agricultural products; hence, the continent is trying to incorporate geographic and regional trading blocs to align them with private- sector partnership programs. The aim of this policy direction is to use territorial comparative advantages to increase market power and share, and promote regional development, which ultimately can lead to country- specific economic development and poverty reduction.